INTEGRATED REPORTING WITHIN THE FRAMEWORK OF INTEGRATION AND STRENGTHENING OF ESG REPORTING: A SYSTEMATIC LITERATURE REVIEW - Tania Haura Azahra; Lovanka Salsabila Aulia Putri; Yusnaini Yusnaini (Jurnal Media Akademik (JMA), 2026)
Rising demands for transparency and accountability have encouraged firms to improve the quality of Environmental, Social, and Governance (ESG) reporting. International Integrated Reporting Council introduced Integrated Reporting as a framework that integrates financial and non-financial information to reflect long-term value creation and strategic sustainability orientation. By linking governance, performance, and future prospects, Integrated Reporting aims to provide a more holistic representation of how organizations create value over time. However, systematic evidence on the role of Integrated Reporting in strengthening and integrating ESG reporting remains limited within the broader sustainability reporting literature. This study reviews and synthesizes existing research on Integrated Reporting and ESG through a Systematic Literature Review (SLR) of reputable national and international journal articles published between 2020 and 2026, using thematic analysis. The findings indicate that Integrated Reporting enhances the consistency, relevance, comparability, and coherence of ESG disclosures while strengthening transparency and accountability for stakeholders. This study contributes by clarifying the conceptual position of Integrated Reporting within the ESG reporting ecosystem and supporting the development of more integrated and decision-useful sustainability reporting practices.